Incidencia del COVID-19 sobre el consumo de agua en los hogares de la ciudad de Loja - Sánchez Eras, Angélica María (2022)
The incidence of COVID-19 on water consumption in homes in the city of Loja has generated environmental contamination, which has affected the environment due to its excessive use. This phenomenon was exacerbated as a result of the biosafety measures implemented by health authorities, which forced the population to take extreme hygiene habits as one of the main preventive measures to avoid the spread of SARS-CoV-2, which generated a increase in drinking water consumption in the city of Loja. This research analyzes the effect of COVID-19 on the consumption of drinking water in the city of Loja, during the period 2018 - 2021, considering data provided by the Municipal Unit of Drinking Water and Sewerage of Loja UMAPAL, in this sense, A quantitative methodology was used, through an econometric model of Autoregressive Distributed Lag (ARDL) time series, using COVID-19 and drinking water consumption as the main variables. The main results derived from this study show that the evolution of the behavior of water consumption is related to the increase in sanitary measures as a preventive measure of COVID19, in this sense, it can be observed that since March 2020, a considerable increase in the consumption of drinking water, the year in which the COVID-19 pandemic began. The critical situation of water resources in the city of Loja has led to changes in population behavior and in its water consumption, which has led to a significant environmental impact. Likewise, it was found that there is a statistically significant relationship between the consumption of drinking water and the effect of the pandemic generated by COVID-19, that is, water consumption is related to an increase in the face of the pandemic. With the results presented, strategies are proposed to improve the drinking water supply and consumption system